Treatment of permanent tracheostomal stenosis with local steroid injection - Toko Shinkai; Kouji Masumoto; Miki Kamiyama; Yudai Goto; Yasunari Tanaka; Kentaro Ono; Tomohiro Aoyama; Kazuki Shirane; Hinako Horiguchi; Nao Tanaka; Takato Sasaki; Fumiko Chiba; et al. (Journal of Pediatric Surgery Case Reports, 2023)
Background: Stenosis of the permanent tracheostoma causes the patient reduced quality of life. We herein report a treatment of permanent tracheostomal stenosis with local steroid injection after laryngotracheal separation in a patient with severe motor and intellectual disabilities. Case presentation: The patient was a 22-year-old woman with congenital myopathy who underwent laryngotracheal separation at the age of 21 years. Tracheostomal enlargement was performed at the age of 22 years. Two months after the operation, permanent tracheostomal stenosis developed owing to a hard cicatricial constriction. Although the size of the tracheostoma decreased, yet the patient did not have any respiratory distress. Therefore, we started local steroid injection therapy using triamcinolone acetonide instead of revision surgery. After those 3 injections, the tracheostomal stenosis was apparently dilated. The patient received this treatment 19 times in 3 years and 4months. She has not needed this treatment in the past 1 year and 8 months. No adverse effect of the corticosteroid was seen during the 5-year period. Conclusions: On the basis of our experience, if patients have no symptoms related to stenotic airway obstruction, triamcinolone acetonide injection therapy, instead of revision surgery, is a simple, safe, and highly effective procedure for permanent tracheostomal stenosis.